The Reduction of Salt in Different Cheese Categories: Recent Advances and Future Challenges - Tidona, Flavio; Zago, Miriam; Carminati, Domenico; Giraffa, Giorgio (Frontiers in Nutrition, 2022)
Public awareness about excessive sodium intake and nutrition claims related to salt content entail the need for food industries to carefully reconsider the composition and processing of high sodium foods. Although in some products the reformulation with alternative ingredients is commonly practiced, in cheese the reduction of salt is still a challenging task, as sodium chloride exerts multiple and fundamental functions. Salt favors the drainage of the residual whey, enhances the taste and the aroma profile, regulates the texture, the final pH, the water activity, and affects the microbial growth. Ultimately, salt content modulates the activity of starter and non-starter lactic acid bacteria during cheese manufacturing and ripening, influencing the shelf-life. Any modification of the salting procedure, either by reducing the level of sodium chloride content or by replacing it with other salting agents, may affect the delicate equilibrium within the above-mentioned parameters, leading to changes in cheese quality. The decrease of Na content may be differently approached according to cheese type and technology (e.g., soft, semi-hard, hard, and mold-ripened cheeses). Accordingly, targeted strategies could be put in place to maintain the overall quality and safety of different cheeses categories.